EFEKTIVITAS MOBILISASI DINI DENGAN PENYEMBUHAN LUKA PASIEN PASCA SECTIO CAESAREA DI RSUP DR M.DJAMIL PADANG TAHUN 2016 - Ria, Trifita; Kustanto, Debby Ratno (Jurnal Kesehatan - STIKes Prima Nusantara, 2017)
Smoking for most Indonesian people is still regarded as normal behavior, part of social life and lifestyle, without understanding the risks and health hazards to themselves and the people and the surrounding community. A survey conducted by the Global Adults Tobacco Survey (GATS) in 2011, the prevalence of smokers in Indonesia rank climbed to number 2 in the world. Therefore, the government passed a law on December 24, 2012, the Government issued Regulation 109/2012 on cigarettes for health therein contained rules that must be obeyed by cigarette manufacturers. The purpose of this study to determine how perceptions ofcurrent smokers through five stages, namely the perception of stimulation-organization interpretation and evaluation-memory and recall. This type of research is research using qualitative methods, from the month of August - September 2016. The primary data obtained through interviews focus group discussion while the secondary data obtained to study the document. Informants in this study were active smokers in the village of Tarok Dipo Guguk Panjang District of Bukittinggi. The results of this study are tobacco consumption by the majority of society into its own phenomenon that is difficult to stop the government's efforts to reduce tobacco consumption society by requiring cigarette manufacturers to include warning labels to cigarettes on the packaging cigarette have indeed been done, but smokers still stubborn to keep doing the habit of smoking, In conclusion, note that consumer understanding of the meaning of the stimulus put on warning labels to cigarettes that they see and experience the past is an important factor in shaping perceptions. each individual interpretation based on past experience and interests. Active smokers in the village of Tarok depot on its common aware of any warning labels to cigarettes and are able to understand the meaning of the warning message.